Experimental study of the effects of fin surface characteristics on defrosting behavior. (22nd January 2015) - Liang, Caihua; Wang, Feng; Lü, Yan; Wu, Chunxiao; Zhang, Xiaosong; Zhang, Youfa
Abstract: The defrosting behavior of an air source heat pump includes melting, drainage and evaporation, which shows different characteristics on fins with different surface characteristics. This paper presents an investigation of the effects of surface characteristics on the defrosting behavior of a fin. A frosting/defrosting experimental system was constructed to implement visual research of the defrosting process on fins with different surface characteristics. The characteristics of frost melting and molten water retention were analyzed and compared. The effects of the surface characteristics on the melting time and melting process were significant. There were obvious differences in molten water retention among different fins. Retained water formed a thin water film on the hydrophilic fin, while only a few spherical droplets with small sizes stayed on the super hydrophobic fin because the frost layer was released from it. The retained water mass on the super hydrophobic fin was the least, which reduced the energy for evaporation. Repeated experiments showed almost the same defrosting behavior as those of the first run. Highlights: The effect of surface characteristics on defrosting behavior of fins was reported. A fin frosting/defrosting experimental system was constructed to realize the visual research of defrosting process. The characteristics of frost melting and molten water retention were analyzed and compared. Results indicate that the hydrophobic fin can improve the defrosting efficiency.